Asian economic integration report 2021 making digital platforms work for Asia and the Pacific. (Metro Manila, Philippines Asian Development Bank, 2021)
The outbreak in 2020 disrupted both supply and demand sides of an interconnected world economy. Asia and the Pacific was not immune as lockdowns and travel and trade restrictions affected nearly all aspects of cross border economic activity. The Asian Economic Integration Report 2021 looks at how regional economies individually or collectively respond to the crisis by, for example, leveraging rapid technological progress and digitalization as well as increasing services trade to reconnect and recover. The theme chapter focuses on digital platforms and how they can accelerate digital transformation across the region.
Keywords: Information technology -- Asia and the Pacific; Asia and the Pacific -- Economic integration; Electronic books